Oxygen sensing in the orchestration of hyрохіс mеtаbolic arrest - Land, Stephen C. (Acta Andina, 2025)
The metabolic and molecular basis of oxygen sensing has been probed using isolated hepatocytes from the vertebrate facultative anaerobe, the western painted turtle. As part of a coordinated systemic response to hypoxia, these cells actively suppress ATP synthesis in synchrony with ATP demand from all major energy sinks (Na+/K+ ATPase, Ca2+ ATPase, protein turnover, urea synthesis, glucose release and gluconeogenesis). The result is a 10-fold suppression in metabolic rate superimposed over a re-partitioning of ATP- demand among cellular processes. This oxygen-dependent metabolic re-organization is tightly controlled, being rapid in onset, occurs without perturbation to adenylate concentrations. or membrane potential, it involves the oxygen-dependent suppression and expression of specific genes and it sustains a new, lower rate of flux through specific biochemical pathways. until re-oxygenation. The net effect dramatically spares fermentable substrate, limits rates of metabolic waste accumulation and profoundly extends survival time in anoxia. Direct roles for oxygen-receptive mechanisms in the control of flux rates have been explored for two energetically significant cellular events during the onset of hypoxic metabolic suppression. Protein turnover, the most energetically eostly cell process in norrnoxia, exhibited oxygen-dependent modulation of specific protein bands whose expression could be predictably manipulated by Co2+, Ni2+, and Co. This supports a role for heme-protein based oxygen receptor mechanism in the control of hypoxic gene expression on entering metabolic arrest. Secondly, noninvasive studies using a Ca2+-selective selfreferencing electrode demonstrate that ther is a 75% suppression in transmembrane Ca2+-flux that is oxygen conforming, exhibiting an apparent KmO2 of 145µM. The suppression of Ca2+-flux was protein kinase-c dependent, and was not repeatable under aerobic inhibition of electron transfer be KCN. These results suggest that the hypoxic response of different cellullar processes coalesce to form a coordinated metabolic and molecular re-orchestration of cell function that enables longterm survival without oxygen. Integral to this is the clear potential for oxygen-receptive mechanisms to signal, and coordinate, flux changes through complex, energetically expensive pathways.